An Educational Intervention to Decrease Drug Costs Related to Terminal Secretions in a Hospice Organization. (2nd January 2017) - Brock, Cara; Cooper, Sarah; Herndon, Christopher M.
ABSTRACT: Terminal secretions is a common symptom seen in hospice patients. Antimuscarinic drugs are commonly used to treat this symptom despite a lack of supporting data. Wide variability in cost exists among these treatments. Hospice program data were assessed to identify high-use and high-cost medications. An educational intervention (EI) was developed to target one such medication, transdermal scopolamine. The EI focused on efficacy, safety, and actual cost (by unit and total expenditure) for each possible treatment of terminal secretions. Following the EI, drug utilization data was re-evaluated. Prior to the deployment of the EI, total monthly hospice drug costs averaged $91, 405 (SD 1, 444) with an average drug cost per patient per day of $11.42 (SD 0.54). Monthly costs of drugs frequently employed to treat terminal secretions averaged $7, 187.67 (SD 2, 253) pre-intervention. Following the EI, monthly drug costs decreased 22.5%, average daily patient drug costs decreased 11.1%, and total anti-secretion costs decreased 28.5% after adjusting for difference in census. Education regarding the use and cost of medications to treat symptoms at end-of-life in hospice patients can be an intervention used to lead to significant cost savings to hospice organizations while maintaining appropriate symptom management for patients. Future interventions to target additional high-cost medications are warranted.